A behaviour change package to prevent hand dermatitis in nurses working in the National Health Service: results of a cluster randomized controlled trial. (1st September 2020) - Madan, I.; Parsons, V.; Ntani, G.; Coggon, D.; Wright, A.; English, J.; McCrone, P.; Smedley, J.; Rushton, L.; Murphy, C.; Cookson, B.; Williams, H.C.
Summary: Background: Occupational hand dermatitis poses a serious risk for nurses. Objectives: To evaluate the clinical and cost‐effectiveness of a complex intervention in reducing the prevalence of hand dermatitis in nurses Methods: This was a cluster randomized controlled trial conducted at 35 hospital trusts, health boards or universities in the UK. Participants were (i) first‐year student nurses with a history of atopic conditions or (ii) intensive care unit (ICU) nurses. Participants at intervention sites received access to a behavioural change programme plus moisturizing creams. Participants at control sites received usual care. The primary outcome was the change of prevalent dermatitis at follow‐up (adjusted for baseline dermatitis) in the intervention vs. the control group. Randomization was blinded to everyone bar the trials unit to ensure allocation concealment. The trial was registered on the ISRCTN registry: ISRCTN53303171. Results: Fourteen sites were allocated to the intervention arm and 21 to the control arm. In total 2040 (69·5%) nurses consented to participate and were included in the intention‐to‐treat analysis. The baseline questionnaire was completed by 1727 (84·7%) participants. Overall, 789 (91·6%) ICU nurses and 938 (84·0%) student nurses returned completed questionnaires. Of these, 994 (57·6%) had photographs taken at baseline and follow‐up (12–15 months). When adjusted for baseline prevalence of dermatitis and follow‐up interval, the odds ratios (95% confidence intervals) for hand dermatitis at follow‐up in the intervention group relative to the controls were 0·72 (0·33–1·55) and 0·62 (0·35–1·10) for student and ICU nurses, respectively. No harms were reported. Conclusions: There was insufficient evidence to conclude whether our intervention was effective in reducing hand dermatitis in our populations. Linked Comment:  Brans. Br J Dermatol 2020; 183:411–412 .